Arterialisation of Great Saphenous Vein in Situ for Limb Salvation: a Case Report - Cvetanovski, Vlatko; Arsovski, Andreja; Stojanovska, Liljana; Cvetanovska, Marija; Dimitrov, Zoran (Lietuvos chirurgija, 2018)
[full article and abstract in English] Abstract. Critical lower limb ischemia in the absence of distal arterial circulation presents an urgent situation, which must be treated immediately if we want to save the foot or limb from amputation. The reduced arterial flow in these situations is not adequate to provide metabolic requirements of lower limb even in rest. According to Fountain these patients are classified in Class III or in Class IV. Approximately 14%–20% of patients with critical lower limb ischemia are unsuited for distal arterial reconstruction and face major distal amputation [1]. Distal venous arterialization is a unique procedure in which the venous bed is used as an alternative conduit for perfusion of peripheral tissues of lower limb. Patients with critical lower limb ischemia can be treated by arterialization of great saphenous vein. Case report. In the present article, we describe the first case of in situ arterialization of great saphenous vein performed inMacedoniain treatment of critical below-knee ischemia. Maintaining the great saphenous vein in situ allows the arterialization of the foot venous arch with one anastomosis without removing the vein of its original bed. Conclusion. Distal revascularization of the limb with critical ischemia, by creating a reverse flow with in situ saphenous vein arterialization must be seriously considered as an attempt for salvage of the foot or below-knee without distal arterial run-off.